Fabrication of anti-fouling PVDF nanocomposite membranes using manganese dioxide nanospheres with tailored morphology, hydrophilicity and permeation. (3rd September 2018) - Sri Abirami Saraswathi, Meenakshi Sundaram; Rana, Dipak; Divya, Kumar; Alwarappan, Subbiah; Nagendran, Alagumalai
Abstract : Manganese dioxide (MnO2 ) nanospheres were prepared by a facile hydrothermal technique and their influence on the permeation and antifouling properties of poly(vinylidene fluoride) (PVDF) ultrafiltration (UF) membranes was investigated. Abstract : Manganese dioxide (MnO2 ) nanospheres were prepared by a facile hydrothermal technique and their influence on the permeation and antifouling properties of poly(vinylidene fluoride) (PVDF) ultrafiltration (UF) membranes was investigated. Different concentrations of MnO2 nanospheres (such as 0.0, 0.5, 1.0 and 2.0 wt%) were added and they were designated as pristine PVDF, PVDF-0.5, PVDF-1 and PVDF-2, respectively. AFM images confirmed that upon increasing the wt% of MnO2 nanospheres, there is an increase in the surface roughness of the PVDF/MnO2 nanocomposite membranes. Further, SEM images revealed the formation of finger-like macrovoids along with improved porosity. Moreover, upon increasing the wt% of MnO2 on PVDF, the pure water flux was enhanced and attains a value of 153.4 Lm −2 h −1 for the PVDF-2 nanocomposite membrane. Fouling experiments were performed using bovine serum albumin (BSA) and humic acid (HA) as model fouling contaminants. Experimental results confirmed that the higher flux recovery ratio (FRR) of the PVDF/MnO2 membranes indicates the enhancement of their hydrophilicity and antifouling ability. Tensile strength results suggested that the PVDF/MnO2 membranes possess improved mechanical resistance compared with the pristine PVDF due to the change in their morphologies. However, increasing the concentration of MnO2 beyond 2% resulted in phase inversion during membrane fabrication and hindered the membrane formation. The results confirmed that the PVDF-2 membrane outperformed other membranes employed in this work in terms of improved permeation and antifouling properties, without compromising the BSA or HA rejection and membrane strength. In light of all these results, it is evident that the MnO2 nanosphere incorporated PVDF nanocomposite UF membrane shows potential for water treatment applications.